Economic, growth performance and heamatological implications of raising Clarias gariepinus advanced fry on high protein diets in concrete homestead ponds (2004)
The commercial production of fish in concrete homestead ponds is fast gaining acceptance in Nigeria, but the growth rate of such is constrained by the stocking of good-sized fingerlings and the availability of quality fish feed. Hence, this study was designed to investigate the economic analysis, growth performance and hematological changes in advanced fry raised on high protein diets in concrete tanks. The design of the experiment is completely randomized and the economic viability of the project was determined by comparing the cost: benefit ratio of the four feeding regimes. One thousand, two hundred Clarias gariepinus advanced fry with initial mean weight of 0.74+0.18g were randomly divided into 4 groups. Three 1m3 net cages were suspended in each tank of (3m x2m x1.5m) dimension. The treatments were fed practical diets containing 40% (control); 48%; 56%; 64% CP levels respectively for 12 weeks. The following parameters were monitored as stated: weight gains (bimonthly); water quality (weekly); haematology (initial and at end of the experiment). carcass analysis at (initial and at end of experiment). Feed conversion ratio, proximate analysis and cost: benefit ratio (were calculated at end of the experiment). Data generated were statistically analyzed using the 2-way analysis of variance (ANOVA) and Duncan's multiple range tests at 95% and 99% confidence limits as appropriate. The results of the study showed that raising of fingerlings in concrete tanks can be enhanced optimally through the feeding of a 48% CP inclusion as against the conventional 40% CP in practical diets used in earthen ponds. The incidence of cost showed that feeding advanced fry on 40% and 48% CP diet are not significantly different but both values are significantly better than fish fed on diet 56% and 64% CP. While the profit index showed that it is more profitable to feed the fish on diets containing either 40%, 48% and 56% CP. However, fish fed on the 48% CP diet in this study had optimum mean weight gain of (9.49g) and the highest PPV value (2.44), which was significantly different from fish, fed 40% (2.41), 56%(0.75) and 64% (1.15). In addition, this research further highlighted the fact that high CP inclusion beyond the optimum does not necessarily give high weight gains nor give the best economic reward because fish diets 3 (56%CP) and diets 4(64%CP) had lower weight gains and lower profit index. There were no appreciable derangements in hematological parameters in fish fed 40%CP and 48% CP. However fish fed 56%CP and 64% CP developed normocytic normochronic anemia and hypoproteinaemia conditions. This implies wastage of resources and confirms that inclusion of CP levels higher than 48% CP in diets of C gariepinus fry had negative effects on haemopoiesis and does not have growth, hematological nor economical advantage in raising advanced fry to fingerling in concrete tanks.